Genome-Wide Identification of the CIPK Gene Family in Jasmine and Expression Analysis Under Salt Stress - Shuang Zhang; Xin Huang; Lili Yin; Jiawei Li; Jiacan Xu; Ruigang Wu (Horticulturae)
Various CBL-interacting protein kinases (CIPKs) are involved in abiotic stress responses in plants. Despite the economic importance of jasmine (Jasminum sambac L. Aiton) and the availability of genome data, there are few reports analyzing the CIPK gene family. In this study, genome-wide identification of the CIPK gene family in jasmine was conducted, which would provide valuable information for the function analysis of JsCIPKs regarding participation in growth and development and response to salt stress. In the present study, a total of 17 CIPKs were identified, which were unevenly distributed on eight chromosomes. The JsCIPK protein sequences contained 311–781 amino acids, with a molecular weight of 35.05–87.58 kDa. Phylogenetic analysis revealed that the 17 JsCIPKs could be divided into five classical branches. JsCIPK genes with higher homology showed greater similarity between conserved protein motifs. Collinearity analysis demonstrated that 13 gene pairs in Arabidopsis were collinear with the jasmine sequences. Various hormone-related response- and stress-induced elements were observed in the promoter region of JsCIPK genes, such as TC-rich repeats, CARE, etc. Furthermore, the expression of JsCIPK genes varied in different organs. Finally, the expression analyses of eight JsCIPKs under salt stress were performed. A systematic analysis of the CIPK gene family and the effect of salt stress on the expression of eight JsCIPK genes in leaves of jasmine was carried out. The expression of JsCIPK6 and JsCIPK8 was significantly down-regulated and up-regulated by salt treatment, respectively. These findings would lay a foundation for future functional studies of these two genes in jasmine related to salt stress and provide useful resistance genes for the molecular breeding of new varieties of salt-tolerant jasmine.